Feasibility of switching from intravenous to subcutaneous immunoglobulin in CIDP: PATH trial and clinical experience. Issue 1 (January 2019) - Cocito, D.; Peci, E.; Lauria Pinter, G.; Dacci, P.; Di Muzio, A.; Telese, R.; Schenone, A.; Benedetti, L.; Antonini, G.; Morino, S.; Sorbi, S.; Matà, S.; et al.
Abstract : The PATH study showed efficacy of subcutaneous IgG administration (SCIG) in chronic inflammatory demyelinating polyneuropathy (CIDP). We evaluated the feasibility of switching from intravenous IgG (IVIG) to SCIG in CIDP patients according to PATH data and clinical experience. In PATH, CIDP patients were randomized to SCIG (0.2 or 0.4 g/kg/week) or placebo after IVIG restabilization. Observational studies of switching from IVIG to SCIG in CIDP and multifocal motor neuropathy are also considered. Forty-eight% of PATH subjects experienced ⩾ 1 adverse event (AE) with IVIG (rate: 0.175/infusion). Corresponding percentages for SCIG-0.2 and SCIG-0.4 were 58% and 52% (0.08 and 0.05/infusion). The most common AE was headache for IVIG (16%), and local infusion site reactions for SCIG (19% and 29%). Most subjects (88%) felt SCIG was easier to use versus IVIG. More subjects (p < 0.005) improved/maintained QoL with SCIG versus placebo. In observational studies, switching from IVIG to SCIG (1–5 infusion[s]/week) was associated with reduced incidence of AEs (22% vs. 1%, and 60% vs. 0%, IVIG vs. SCIG), improved QoL and higher patient preference for SCIG versus IVIG (69–90%). The PATH trial and observational studies document the feasibility, safety and efficacy of SCIG therapy in CIDP.